KETERKAITAN ANTARA SANITASI PONDOK PESANTREN DENGAN KEJADIAN PENYAKIT YANG DIALAMI SANTRI DI PONDOK PESANTREN SUNAN DRAJAT - Agus Aan Adriansyah (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
Health requirements boarding school environment basically consists of a few things such as construction and general sanitary conditions, basic sanitation facilities, food management, and so on. With good environmental health, health risks and other risks will be avoided. Almost 80% of disease in the boarding school due to the health condition of the environment. Good conditions will also improve the aesthetics of the boarding school. This research was analitic study that held observationally with cross sectional design and used quantitative approach. Sample in this research was male religious pupil of Sunan Drajat Islamic Boarding School with MTS level of education. Sample numbers were 97 religious pupil that was collected from population with proportional random sampling. Variable test held using correlation analysis method. Correlation test results or the r value indicates the value of 0.792. Thus it can be interpreted that there is a strong relationship between sanitation and disease incidence in Pondok Pesantren Sunan Drajat. Therefore, it is necessary to increase the quality and quantity of islamic boarding school sanitation to increase the health of religious pupil. The method that can be done is by providing the islamic boarding school facilities or religious pupil room that appropriate with standard and the improvement of basic sanitation facilities of islamic boarding school such as the providing of bathroom/toilet.